Sigmoid incision rescue nasoseptal flap technique for endoscopic endonasal skull base surgery. (2nd June 2016) - Ozawa, Hiroyuki; Tomita, Toshiki; Watanabe, Yoshihiro; Sekimizu, Mariko; Ito, Fumihiro; Ikari, Yuichi; Saito, Shin; Toda, Masahiro; Ogawa, Kaoru
Abstract: Conclusion The sigmoid-incision (S-I) rescue flap technique has the advantage of both reduced-invasiveness and providing a sufficient surgical corridor for endoscopic endonasal skull base surgery (EESBS).Objective Skull base reconstruction with nasoseptal flap (NSF) is critically important in managing post-operative cerebrospinal fluid (CSF) leakage after tumor removal by EESBS. The NSF needs to be elevated before sphenoidotomy and posterior septectomy to preserve the pedicle. However, most extradural surgery without CSF leakage does not require NSF and, therefore, NSF preparation is often futile. As a result, a rescue flap technique to overcome this problem has been developed, whereby a new S-I rescue flap method is used that enables wide exposure of the sphenoidal rostrum and smooth manipulation of surgical instruments to preserve the NSF pedicle.Materials and methods Starting in April 2014, 19 cases underwent EESBS with S-I rescue flap.Results All patients underwent tumor resection under an adequate operative field with smooth manipulation of surgical instruments. Two complications were experienced. One patient had CSF leak after removal of the nasal packing, but the leakage was successfully closed by conventional NSF. Another patient had epistaxis from the septal wall, but this was controlled by electrocautery.